Kolaborasi Kelompok Usaha Bersama (KUB) “Perempuan Rengganis” dalam Meningkatkan Kesejahteraan Ekonomi Desa Klungkung - Husniah, Furoidatul; Umniyyah, Zahratul; Taufiq, Akhmad; Dwi Eriyanti, Linda; Makmur, M. Hadi; Rohman, Hermanto; Prasetyowati, Irma (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
This study uses a qualitative descriptive method with a case study approach. Data were obtained through direct observation and in-depth interviews with the administrators and members of KWT, RDS, and village officials. The results of the study indicate that the formation of the Joint Business Group (KUB) "Perempuan Rengganis" is a solution to increasing the scale of production, efficiency, and skills of members through training. KUB also strengthens the negotiating position in obtaining support from external parties. Through the utilization of land to plant vegetables and herbal plants, village women are able to improve family welfare and contribute to the local economy. In conclusion, mentoring and synergy efforts between women's business groups in Klungkung Village are able to maximize local potential and empower women to achieve economic independence.